Socieconomic Characteristics of Individuals Afflicted by AIDS-Related Prime-Age Mortality in Zambia - Chapoto, Antony; Jayne, Thomas S. (International Food Policy Research Institute, 2006)
Campaigns to prevent the spread of HIV/AIDS require accurate knowledge of the characteristics of those most likely to contract the disease. Studies conducted in Sub-Saharan Africa during the 1980s generally found a positive correlation between socioeconomic characteristics such as education, income, and wealth and subsequent contraction of HIV (see Ainsworth and Semali 1998; Gregson, Waddell, and Chandiwana 2001). However, as the disease has progressed, the relationship between socioeconomic status and HIV contraction may have changed in many areas of Sub-Saharan Africa, although there is little hard evidence to support this. For example, it is increasingly believed that poverty forces some household members to adopt more risky behaviors that contribute to HIV infection, which could mean that AIDS-related mortality is disproportionately affecting relatively poor households. This chapter seeks to determine the ex ante socioeconomic characteristics of individuals who die between the ages of 15 and 59 years of age (hereafter called “prime-age” mortality), using nationally representative panel data on 18,821 individuals in 5,420 households surveyed in 2001 and 2004 in rural Zambia. We estimate several probit models of disease-related mortality of prime-age (PA) individuals in rural Zambia between May 2001 and May 2004. The results of these models are used to report the probabilities of mortality over a three-year period for a range of individual profiles that differ according to their gender, level of income, education, months residing away from home, distance to district town, and other individual and household characteristics.